Sengkulun as Betawi Traditional Cake Philosophy, Historical and Cultural Review - Tanius, Billy; Sinaga, Tiurma; Brahmantyo, Himawan (E-Journal of Tourism, 2018)
Betawi has a diversity of traditional food. One of the diversity of traditional foods of Betawi’s type of cake is Sengkulun cake. This rare cake is made from glutinous rice flour. Study was designed to recognize the Sengkulun cake from history, culture and philosophy as well as documenting the original way of making the cake which has begun to be forgotten. Descriptive qualitative approach was used to analyse data and information. Respondent were elders, i.e. Betawi cultural experts and Sengkulun cake makers. Experiment was conducted to obtain documentation in the form of photo and video which could make the cake more interesting to become Betawi ‘s snacks. Results show that the Sengkulun cake has existed for a long time but cannot be known with certainty the year of the creation of this cake. This cake began to be created because of the abundant availability of glutinous rice and also due to the influence of Chinese ethnic in the processing the snacks. The cake has a high position in ancient times because this cake can only be found in certain events such as Eid al-Fitr. From the Sengkulun's philosophy, it can be said that sticky texture of the Sengkulun cake has a symbol of respect each other. Keywords: philosophy, Sengkulun, traditional cake